2021
DOI: 10.3390/su13073720
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Authenticity of Naxi Music in Three Stages from the Perspective of Naxi Musicians: An Application of Lacan’s Mirror Stage Theory

Abstract: How do people evaluate the transformation of a local music scene under tourism? Using Jacques Lacan’s mirror stage theory, Manuel Castells’ identity theory and Erik Cohen’s authentication theory, we build a framework to judge the authenticity of Naxi music in Lijiang, China, based on interviews, literature analysis and performance analysis. The conclusions are as follows. First, there are significant differences in authenticity among the three stages of Naxi music, as defined by Lacan’s theory. Second, we modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
(63 reference statements)
0
0
0
Order By: Relevance
“…In contrast, Li and Zhou's study found that local music under tourism is not affected by tourists if it is grounded in the local music culture itself. This suggests that in rapidly changing modern society, ICH should still be grounded in local culture, and the opportunities provided by technology should rely on regional identity for sustainable development [47]. Therefore, the foundation of ICH is rooted in locality.…”
Section: Intangible Cultural Heritagementioning
confidence: 99%
“…In contrast, Li and Zhou's study found that local music under tourism is not affected by tourists if it is grounded in the local music culture itself. This suggests that in rapidly changing modern society, ICH should still be grounded in local culture, and the opportunities provided by technology should rely on regional identity for sustainable development [47]. Therefore, the foundation of ICH is rooted in locality.…”
Section: Intangible Cultural Heritagementioning
confidence: 99%
“…The folk intangible cultural heritage music in China is a music that expresses its emotional life in its own unique way. It is a music culture created by people of all ethnic groups with strong local characteristics and distinct characteristics of the times and has a strong artistic appeal and aesthetic value(D. Li and Zhou, 2021). Since ancient times, due to the unique geographical location and regional environment, as well as the complex and diverse historical and cultural background, Guangxi has formed a rich and exquisite ethnic regional culture, leaving behind many precious and dazzling intangible cultural heritage.…”
Section: Introductionmentioning
confidence: 99%